HUBUNGAN PENGETAHUAN PASIEN TENTANG KEMOTERAPI DENGAN KECEMASAN DALAM MENJALANI TINDAKAN KEMOTERAPI DI RSUD PANEMBAHAN SENOPATI BANTUL - Bayu Teovilus; Dwi Kartika Rukmi; Umi Istianah (Universitas Jenderal Achmad Yani Yogyakarta, 2015)
Background: Chemotherapy is the administration of anti-neoplastic drugs that can cause tumor regression and inhibit its metastasis. Chemotherapy has several effects, both physically and psychologically. One of the most frequent psychological effect of chemotherapy is anxiety. Patients with excessive anxiety l e v e l require assistance from the nurse with the adequate information. Objective: To determine the relationship between the knowledge level on chemotherapy and the anxiety level in carrying out chemotherapy at Panembahan Senopati Hospital Bantul. Method: This research was a descriptive study with cross-sectional design. The reserach used a purposive sampling technique which employed 49 respondents. Data were collected with a questionnaire. The data was analysed with Kendall's Tau test. Results: There was a relationship between the knowledge level on chemotherapy and anxiety level in patients who under went chemotherapy at Panembahan Senopati Hospital Bantul. Kendall's Tau test resulted a significant level of 0.00 (p<0.05) with a correlation coefficient value of 0.605, which showed a strong relationship. Conclusion: There was a significant relationship between the knowledge level on chemotherapy and the anxiety level in patients who underwent chemotherapy at Panembahan Senopati Hospital Bantul. Keywords: Knowledge, Anxiety, Chemotherapy